Internet without wires - Tothill, Ann (Technical Centre for Agricultural and Rural Cooperation, 2006)
African communities without access to the internet are being trained to build their own wireless networks, thanks to a project launched by the South-Africa-based NGO, the Association for Progressive Communications (APC)...